PENDATAAN DAN DIGITALISASI NASKAH KUNO MELAYU DI KABUPATEN KAMPAR - Evizariza, Evizariza; Idayanti, Iik (Universitas Lancang Kuning, 2017)
Manuscript is a cultural heritage of ancestors in the past. In the manuscripts there are many sources of information and knowledge of the community that were developing at that time. One of which was Malay manuscripts. Currently, the existence of Malay manuscripts is widely spread and recorded in various regions, both inside and outside the country. However, there are still many Malay manuscripts that are still owned by individuals, becoming private collections, such as Malay manuscripts in the Kampar region. These manuscripts are still unrecorded and in vulnerable conditions with damage and even lost or sold. Judging from these realities, actions are needed to save the manuscripts, such as collecting and digitalizating. By so, eventhough saving the manuscripts physically is hard, but we can get the contents of the text. Thus, the research on the physical obejct will be studied using a codicological approach, and the text content will be analyzed philologically.